Trade and customs procedures: the compliance costs for UK meat imports: a case study - Grainger, Andrew (Nottingham University Business School, 2013)
The study was funded by the Nottingham University Business School with the support of the International Meat Trade Association (IMTA) and the Association of Port Health Authorities (APHA), amongst others. It involved: a detailed review of current import procedures applicable to importing meat into the United Kingdom (UK) from outside of the European Union (EU); an in-depth study of the trade and customs compliance costs as experienced by three meat importers of chilled and frozen beef and lamb (each importing meat worth more than £100million per year) as well as those of two freight forwarders (agents) specialising in the meat trade; and field visits to the port health inspection facilities (so called Border Inspection Posts, BIPs) at two major UK ports. Cost findings have been confirmed by the IMTA secretariat as being representative (with the caveat that they are subject to market dynamics and the commercial relationships between importers, shippers, shipping lines, ports and agents).